Pembelajaran Tata Letak Fasilitas Guna Meminimalisir Waktu Proses Produksi Pada TEFA SMK Manbaul Ulum - Moh. Jufriyanto; Deny Andesta; Elly Ismiyah; Misbah Misbah; Ahmad Fauzal Ibnu Malik; Fahrizal Hamdani (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
The layout of facilities in the industrial world greatly affects the production process of a product. If the spatial layout used is good and appropriate, it will indirectly save distance, costs, time, and effort. Community service activities are carried out in partnership with SMK Manbaul Ulum. These activities aim to provide learning about facility layout to minimize production process time. The expected outcome of these activities is that students will be able to understand how to reduce excessively long production times and increase the number of products in a business unit, which impacts student productivity. The implementation methods include delivering material, simulating the production process layout, and conducting Q&A discussions. As a result, the activities are able to enhance students' understanding of the importance of layout in production facilities. Students can also simulate the production process to evaluate the existing layout in order to minimize production time. This activity has an impact on decision-making and problem-solving.